Downregulation of Vascular Hemeoxygenase-1 Leads to Vasculopathy in Systemic Sclerosis - Ross, Rebecca L; Mavria, Georgia; Del Galdo, Francesco; Elies, Jacobo (Frontiers in Physiology, 2022)
Systemic sclerosis (SSc) is a terminal disease characterized by vasculopathy, tissue fibrosis, and autoimmunity. Although the exact etiology of SSc remains unknown, endothelial dysfunction, oxidative stress, and calcium handling dysregulation have been associated with a large number of SSc-related complications such as neointima formation, vasculogenesis, pulmonary arterial hypertension, impaired angiogenesis, and cardiac arrhythmias. Hemeoxygenase-1 (HO-1) is an antioxidant enzyme involved in multiple biological actions in the cardiovascular system including vascular tone, angiogenesis, cellular proliferation, apoptosis, and oxidative stress. The aim of this work was to investigate the physiological role of HO-1 and its relevance in the cardiovascular complications occurring in SSc. We found that, in early phases of SSc, the expression of HO-1 in dermal fibroblast is lower compared to those isolated from healthy control individuals. This is particularly relevant as reduction of the HO-1/CO signaling pathway is associated with endothelial dysfunction and vasculopathy. We show evidence of the role of HO-1/carbon monoxide (CO) signaling pathway in calcium handling. Using an in vitro model of pulmonary arterial hypertension (PAH) we investigated the role of HO-1 in Ca2+ mobilization from intracellular stores. Our results indicate that HO-1 regulates calcium release from intracellular stores of human pulmonary arterial endothelial cells. We interrogated the activity of HO-1 in angiogenesis using an organotypic co-culture of fibroblast-endothelial cell. Inhibition of HO-1 significantly reduced the ability of endothelial cells to form tubules. We further investigated if this could be associated with cell motility or migration of endothelial cells into the extracellular matrix synthesized by fibroblasts. By mean of holographic imaging, we studied the morphological and functional features of endothelial cells in the presence of an HO-1 activator and selective inhibitors. Our results demonstrate that inhibition of HO-1 significantly reduces cell proliferation and cell motility (migration) of cultured endothelial cells, whilst activation of HO-1 does not modify either morphology, proliferation or motility. In addition, we investigated the actions of CO on the Kv7.1 (KCQN1) channel current, an important component of the cardiac action potential repolarization. Using electrophysiology (whole-cell patch-clamp in a recombinant system overexpressing the KCQN1 channel), we assessed the regulation of KCQN1 by CO. CORM-2, a CO donor, significantly reduced the Kv7.1 current, suggesting that HO-1/CO signaling may play a role in the modulation of the cardiac action potential via regulation of this ion channel. In summary, our results indicate a clear link between: 1) downregulation of HO-1/CO signaling; and 2) pathophysiological processes occurring in early phases of SSc, such as calcium homeostasis dysregulation, impaired angiogenesis and cardiac arrhythmias. A better understanding of the canonical actions (mainly due to the biological actions of CO), and non-canonical actions of HO-1, as well as the interaction of HO-1/CO signaling with other gasotransmitters in SSc will contribute to the development of novel therapeutic approaches.